Notary’s Role & Responsibilities in the Implementation of Association Registration through Online Legal Entity Administration System - Abdul Hasim; Gunarto Gunarto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to analyze role and responsibilities of a notary and the procedure for registering associations through the online Legal Entity Administration System. The approach method in this research was a sociological juridical approach. The data used were primary data and secondary data obtained through interviews and literature study, data analysis was carried out in a descriptive analytical manner. The results of the study concluded the association registration procedure through the online Legal Entity Administration System is uncomplicated and the procedure begins with an application for ordering the name of the association through SABH www.ahu.go.id, then the application for legalization of the association's legal entity must be submitted by a notary with supporting documents submitted electronically. Supporting documents in the form of an electronic statement from the applicant. A statement letter containing the completeness of the association's establishment documents from the applicant. The Ministerial Decree concerning the legalization of the association legal entity is issued no later than 14 days. The period of time is calculated from the date of the statement of no objection from the Minister. The fee for ordering the name of the association is IDR 100,000, -, while for the ratification of the establishment of the association of IDR 250.000,-.